2012
DOI: 10.1158/1535-7163.mct-11-0977
|View full text |Cite
|
Sign up to set email alerts
|

O(6)-Methylguanine-DNA Methyltransferase Is a Novel Negative Effector of Invasion in Glioblastoma Multiforme

Abstract: The dismal prognosis of glioblastoma multiforme (GBM) is mostly due to the high propensity of GBM tumor cells to invade. We reported an inverse relationship between GBM angiogenicity and expression of the DNA repair protein O 6 -methylguanine-DNA methyltransferase (MGMT), which has been extensively characterized for its role in resistance to alkylating agents used in GBM treatment. In the present study, given the major role of angiogenesis and invasion in GBM aggressiveness, we aimed to investigate the relatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Some synergism was observed in the U87MG-luc2 cell line (MGMT-expressing) as also previously reported ( Voss et al , 2010 ). Nevertheless, U373 (MGMT-low level) and U251 (MGMT-negative) GBM cell lines ( Chahal et al , 2012 ) demonstrated additive and antagonistic response to combined drug treatment. Interestingly, it has previously been reported that U251 and U373 GBM cell line express low Mcl-1 levels ( Day et al , 2011 ), whereas U87 and U343 cell lines exhibit high Mcl-1 expression levels ( Hetschko et al , 2008 ; Day et al , 2011 ; Murphy et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some synergism was observed in the U87MG-luc2 cell line (MGMT-expressing) as also previously reported ( Voss et al , 2010 ). Nevertheless, U373 (MGMT-low level) and U251 (MGMT-negative) GBM cell lines ( Chahal et al , 2012 ) demonstrated additive and antagonistic response to combined drug treatment. Interestingly, it has previously been reported that U251 and U373 GBM cell line express low Mcl-1 levels ( Day et al , 2011 ), whereas U87 and U343 cell lines exhibit high Mcl-1 expression levels ( Hetschko et al , 2008 ; Day et al , 2011 ; Murphy et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of MMP-2 with α5β1 integrin was shown to regulate the IL-6/STAT3 survival signaling in glioma [115]. The expression of the DNA repair protein, O6-Methylguanine-DNA Methyltransferase (MGMT), was inversely related to invasion capacity of glioma and to α5β1 integrin expression [116]. …”
Section: Integrin α5β1 In Solid Tumorsmentioning
confidence: 99%
“…Cell migration and invasion was assessed using modified Boyden chambers (8-mm pore, BD Biosciences, CA) according to previously established methods. 34 Chambers were either non-coated for migration or pre-coated with BD Matrigel basement membrane for invasion studies. Assays were performed 5 d after exposure to AIR or FIR.…”
Section: Migration and Invasion Assaysmentioning
confidence: 99%